Technical, Non-technical, and Other Skills Needed by Canadian Mining, Petroleum and Public Sector Organizations - Heath, C. (Geoscience Canada, 2002)
Summary Events of the last decade have forced Canada's geoscience community to restructure, refocus on core businesses, and devise new strategies. These require new technologies to replace the old. Using 1996-1997 data collected from 21 large mining and oil companies and five public sector organizations, the author identifies, assesses, and ranks about 150 geoscience sub-disciplines, computer skills, non-technical and soft skills, and also evaluates mathematics, language, and business requirements. Geoscience skills comprise about 50% of the entire skill profile. Computer skills ( 16%) are highly transferable to alternative careers. Non-technical and softskills (34%) are also essential. The teaching-learning process develops some non-technical and soft skills although many of them seem to be innate. Although students and alumni wanted more language education at university, executives seemed lukewarm to language skills. Most respondents wanted some business education to be included in curricula: sodid alumni and students. New external forces now influence education and recruiting. These include a more sophisticated and global recruiting process and an expectation that recruits have higher qualifications and industry-related work experience. The need for all geoscience stakeholders to work together in the preparation of young geoscientists has become essential.